1993
DOI: 10.1007/bf01552161
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of an ACL disruption with KT-1000 arthrometer measurements

Abstract: The KT-1000 was used to measure anterior tibial displacement in three populations: normal subjects (n = 120), patients with unilateral acute anterior cruciate ligament (ACL) disruptions (n = 105), and patients with chronic unilateral ACL disruptions who were scheduled for ACL reconstructions (n = 159). All patients with ACL disruptions were measured with and without anesthesia. Tibial displacement under three loading conditions was measured: 89-N anterior displacement force, manual maximum displacement force, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 49 publications
(56 reference statements)
2
66
0
4
Order By: Relevance
“…They determined that there is no difference between two groups on their "one leg" balance test (45). A certain tendency to better balance in the nonpreferred leg was observed, some authors did not demonstrated differences between dominant and nondominant extremities in athletes (2,16,31). It is stated that none of the tests performed revealed statistically significant differences in balance ability between the preferred and the nonpreferred leg (22).…”
Section: Discussionmentioning
confidence: 99%
“…They determined that there is no difference between two groups on their "one leg" balance test (45). A certain tendency to better balance in the nonpreferred leg was observed, some authors did not demonstrated differences between dominant and nondominant extremities in athletes (2,16,31). It is stated that none of the tests performed revealed statistically significant differences in balance ability between the preferred and the nonpreferred leg (22).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the limits of the initial tension provided a match in anterior laxity to within 1 mm of that of the intact knee throughout the range of stiffness encompassing commercially available fixation methods (Table 1). A I-mm match is within the 2-3 mm difference in anterior laxity between left and right pairs of intact knees [11,32].…”
Section: Methodological Issuesmentioning
confidence: 99%
“…seven males and three females, 26.3k 12 years) based on a screening examination [8]. A positive Lachman test, > 3 mm side-to-side difference measured with KT 1000 arthrometer (Medmetric, San Diego, CA) [21], and magnetic resonance imaging confirmed ACL rupture. In addition, 10 individuals (six males and four females, 23 k6.5 years) without any significant injuries to either lower extremity were tested as a comparison group.…”
Section: Subjectsmentioning
confidence: 99%